2018
DOI: 10.3389/fnins.2018.00136
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenomic Profiling Reveals Distinct Gene Expression Profiles Between Brain Parts That Are Consistent in Ophthalmotilapia Cichlids

Abstract: The detection of external and internal cues alters gene expression in the brain which in turn may affect neural networks that underly behavioral responses. Previous studies have shown that gene expression profiles differ between major brain regions within individuals and between species with different morphologies, cognitive abilities and/or behaviors. A detailed description of gene expression in all macroanatomical brain regions and in species with similar morphologies and behaviors is however lacking. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Only eight genes were differentially expressed in both tissues. This low overlap is not surprising considering the demonstrated differences in the expression of activity-regulated genes across brain regions in birds and fish10,39. Even though evolutionary models predict sex linkage of female preference genes under the good genes model40,41, we did not observe an enrichment of these candidate genes on the X chromosome (LG12, P>0.05).…”
Section: Resultsmentioning
confidence: 50%
“…Only eight genes were differentially expressed in both tissues. This low overlap is not surprising considering the demonstrated differences in the expression of activity-regulated genes across brain regions in birds and fish10,39. Even though evolutionary models predict sex linkage of female preference genes under the good genes model40,41, we did not observe an enrichment of these candidate genes on the X chromosome (LG12, P>0.05).…”
Section: Resultsmentioning
confidence: 50%
“…[31][32][33] Mounting evidence suggests, however, that patterns of gene expression vary among subdivisions of the vertebrate brain. [34][35][36][37] For example, studies of birds and mammals have showed distinctive gene expression profiles in the amygdala and hypothalamus, [38][39][40] suggesting that suites of behaviorally relevant genes are differentially expressed among nodes of the SBN. Indeed, results from candidate gene studies have showed that expression levels of key neuroendocrine genes can vary widely across regions of the SBN and that relationships between neuroendocrine gene expression and behavior are region-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of studies have leveraged whole‐brain transcriptomic data to identify the gene expression profiles associated with sex, social status, ecotype and reproductive strategy within species, as well as interspecific differences in reproductive and social behaviors across species . Mounting evidence suggests, however, that patterns of gene expression vary among subdivisions of the vertebrate brain . For example, studies of birds and mammals have showed distinctive gene expression profiles in the amygdala and hypothalamus, suggesting that suites of behaviorally relevant genes are differentially expressed among nodes of the SBN.…”
Section: Introductionmentioning
confidence: 99%